2016
DOI: 10.1002/biot.201600332
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence colocalization microscopy analysis can be improved by combining object‐recognition with pixel‐intensity‐correlation

Abstract: The question whether two proteins interact with each other or whether a protein localizes to a certain region of the cell is often addressed with fluorescence microscopy and analysis of a potential colocalization of fluorescence markers. Since a mere visual estimation does not allow quantification of the degree of colocalization, different statistical methods of pixel‐intensity correlation are commonly used to score it. We observed that these correlation coefficients are prone to false positive results and ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 23 publications
0
60
0
Order By: Relevance
“…Gels were imaged at 40X to a depth of 25 µm, which is the approximate depth of a single vessel. A region of interest (ROI) was drawn around vascular structures, and signal overlap between αSMA and isolectin B4 were quantified for the ROI using Manders coefficients as determined by the Fiji plugin coloc2 (62).…”
Section: Staining Imaging and Image-based Analysesmentioning
confidence: 99%
“…Gels were imaged at 40X to a depth of 25 µm, which is the approximate depth of a single vessel. A region of interest (ROI) was drawn around vascular structures, and signal overlap between αSMA and isolectin B4 were quantified for the ROI using Manders coefficients as determined by the Fiji plugin coloc2 (62).…”
Section: Staining Imaging and Image-based Analysesmentioning
confidence: 99%
“…4B, white arrows). We performed the co-localization analysis for AGEs+actin and AGEs+tubulin for glycation by coloc2 plugin in Fiji on the background subtracted images (55). It was observed that Pearson's Co-Correlation Co-efficient (PCC) for actin+AGEs was increased in presence of MG suggesting actin glycation.…”
Section: Egcg Inhibits Glycation Of Actin and Tubulin Cytoskeletonmentioning
confidence: 99%
“…To ensure the glycation of cytoskeleton, co-localization analysis was carried out for AGEs (red) and actin (green) and AGEs (red) tubulin (green) fluorescence. The analysis was carried out on the background subtracted images the reported algorithm (55). The Pearson's coefficient of correlation was determined by the coloc-2 plugin of Fiji software.…”
Section: Co-localization Analysismentioning
confidence: 99%
“…Treatment options for these and other diseases often rely on detailed analysis of cellular signaling. Moser et al [7] provide now a method to improve fluorescence colocalization microscopy analysis, which can be used to show whether two proteins interact with each other.…”
Section: Jing Zhu and Uta Goebelmentioning
confidence: 99%